Predictive value of hypoglycin A and methylencyclopropylacetic acid conjugates in a horse with atypical myopathy in comparison to its cograzing partners. (7th June 2016) - Bochnia, M.; Scheidemann, W.; Ziegler, J.; Sander, J.; Vollstedt, S.; Glatter, M.; Janzen, N.; Terhardt, M.; Zeyner, A.
Summary: Hypoglycin A (HGA) was detected in blood and urine of a horse suffering from atypical myopathy (AM; Day 2, serum, 8290 μg/l; urine: Day 1, 574, Day 2, 742 μg/l) and in its cograzing partners with a high variability (46–1570 μg/l serum). Over the period of disease, the level of the toxic metabolites (methylencyclopropylacetic acid [MCPA]‐conjugates) increased in body fluids of the AM horse (MCPA‐carnitine: Day 2, 0.246, Day 3, 0.581 μmol/l serum; MCPA‐carnitine: Day 2, 0.621, Day 3, 0.884 μmol/mmol creatinine in urine) and HGA decreased rapidly (Day 3, 2430 μg/l serum). In cograzing horses MCPA‐conjugates were not detected. HGA in seeds ranged from 268 to 367 μg/g. Although HGA was present in body fluids of healthy cograzing horses, MCPA‐conjugates were not detectable, in contrast to the AM horse. Therefore, increasing concentrations of MCPA‐conjugates are supposed to be linked with the onset of AM and both parameters seem to indicate the clinical stage of disease. However, detection of HGA in body fluids of cograzing horses might be a promising step in preventing the disease.